Metastatic small bowel adenocarcinoma in a 10-year-old Chinese girl - Y.C.L. Leung; L.Y. Chung; C.S.W. Liu; J.W.S. Hung; P.M.Y. Tang; N.S.Y. Chao; M.W.Y. Leung; K.K.W. Liu (Elsevier, 2015)
Small bowel adenocarcinoma is a rare entity in both adult and paediatric populations. Diagnosis is usually delayed due to vague symptoms. We report a case of ileal adenocarcinoma presented with multiple metastases. A 10-year-old Chinese girl presented with recurrent right lower quadrant pain developed intestinal obstruction. Computerized tomography showed terminal ileum wall thickening, a pelvic mass and suspicious pulmonary metastases. Laparotomy showed a terminal ileal tumour causing mechanical obstruction with metastases to the left ovarian and mesenteric lymph nodes. Palliative right hemi-colectomy with double-barrel ileostomy was performed. The pathology was reported to be ileocaecal adenocarcinoma with extensive lymphovascular permeation. She was the started on palliative chemotherapy with static disease. Diagnosis of small bowel adenocarcinoma remains a challenge to surgeons as the clinical presentation is subtle in spite of the advanced clinical course. Surgery plays a role in symptomatic treatment for patients with intestinal obstruction in advanced stage.